2002
DOI: 10.1017/s0317167100001803
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Neuropathogenesis of Molybdenum Cofactor Deficiency

Abstract: 91Molybdenum is found in most foods including legumes, dairy products and meats. It is an important element that forms a complex called molybdenum cofactor. Three mammalian enzymes depend on this cofactor for their function. These enzymes are (i) sulphite oxidase, a terminal enzyme, essential for detoxifying sulphites; (ii) xanthine dehydrogenase, which plays a role in purines metabolism and the formation of uric acid from xanthine and hypoxanthine and (iii) aldehyde dehydrogenase, which catalyses the conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…13 In addition, the cortex area near the cysts did not show restricted diffusion; therefore, the insult to areas with subcortical cysts is thought to start before birth. Neuropathological findings of cortical necrosis and extensive cavitating leukoencephalopathy were reminiscent of those in severe perinatal asphyxia, suggesting an etiology of energy deficiency in MoCoD 14 and ISOD. 15 The sulfite oxidase enzyme is located in the mitochondrial intermembranous space and is involved in electron transfer from sulfites into the electron transport chain.…”
Section: Figurementioning
confidence: 90%
“…13 In addition, the cortex area near the cysts did not show restricted diffusion; therefore, the insult to areas with subcortical cysts is thought to start before birth. Neuropathological findings of cortical necrosis and extensive cavitating leukoencephalopathy were reminiscent of those in severe perinatal asphyxia, suggesting an etiology of energy deficiency in MoCoD 14 and ISOD. 15 The sulfite oxidase enzyme is located in the mitochondrial intermembranous space and is involved in electron transfer from sulfites into the electron transport chain.…”
Section: Figurementioning
confidence: 90%
“…In other cases of molybdenum cofactor deficiency, which would compromise SO activity, data from magnetic resonance imaging also suggested hypoxic-ischemic encephalopathy (43). It was proposed that neuronal injury was caused by mitochondrial damage by sulfite, which disrupts mitochondrial membrane integrity leading to decreased ATP or energy failure (44). From these noninvasive studies, it was concluded that the underlying cause was a dysfunction of brain mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamine is an abundant amino acid in the brain, and it can be converted to glutamate, which is present in severalfold higher concentrations than the Krebs cycle metabolites; it therefore contributes significantly to mitochondrial respiratory function. Inhibition of GDH by an accumulation of sulfite in the brain of subjects with human SO deficiency would conceivably cause an energy crisis as shown in MR imaging (42)(43)(44). With inhibition of GDH by sulfite, the supply of ␣-ketoglutarate would be curtailed, because in the brain the GDH reaction operates in the direction of oxidative deamination to form ␣-ketoglutarate (48).…”
Section: Nadmentioning
confidence: 99%
“…However, the molecular mechanisms involved are not fully understood. In clinical studies of SO and molybdenum cofactor deficiencies, it was proposed that neuronal toxicity was due to decreased ATP or energy deficit/failure [82,83]. It has also been suggested that excess sulfite might damage mitochondrial function via disruption of membrane integrity [9,84].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid-dependent asthmatics and children with chronic asthma are especially vulnerable to such toxicity [2]. Sulfite is also toxic to neurons and cardiovascular system [9][10][11][12][13][14]. The level of sulfite in serum was found to be unregulated in several disease conditions, such as pneumonia and end-stage renal failure [15,16].…”
Section: Introductionmentioning
confidence: 99%